Transoral laser microsurgery for oropharyngeal squamous cell carcinoma: A paradigm shift in therapeutic approach. Issue 8 (4th April 2016) - Wilkie, Mark D.; Upile, Navdeep S.; Lau, Andrew S.; Williams, Stephen P.; Sheard, Jon; Helliwell, Tim R.; Robinson, Max; Rodrigues, Jennifer; Beemireddy, Krishna; Lewis–Jones, Huw; Hanlon, Rebecca; Husband, David; et al.
Abstract: Background: The contemporary treatment of oropharyngeal squamous cell carcinoma (SCC) is an area of debate. We report outcomes of a minimally invasive approach involving transoral laser microsurgery (TLM). Methods: A consecutive series of patients ( n = 153) undergoing primary TLM for oropharyngeal SCC from 2006 to 2013 was studied. Human papillomavirus (HPV) status was determined by p16 immunohistochemistry and high‐risk HPV DNA in situ hybridization. Survival analyses were evaluated using Kaplan–Meier statistics. Results: Tumor subsites included tonsil ( n = 94; 61.5%), tongue base ( n = 38; 24.8%), and soft palate ( n = 21; 13.7%), with the majority being American Joint Committee on Cancer (AJCC) stage III/IVa ( n = 124; 81.0%) and HPV‐positive ( n = 101; 66.0%). Three‐year overall survival (OS), disease‐specific survival (DSS), and disease‐free survival (DFS) were 84.5%, 91.7%, and 78.2%, respectively. HPV‐positivity portended favorable oncologic outcomes. One‐year gastrostomy tube (G‐tube) dependency was 1.3%. Conclusion: To the best of our knowledge, this is the largest single‐center TLM oropharyngeal SCC series to date. Our data suggest that TLM +/− postoperative radiotherapy (PORT) results in at least as good oncologic outcomes as chemoradiotherapy (CRT), while conferring swallowing function advantages. © 2016 Wiley Periodicals, Inc. Head Neck, 2016 © 2016 Wiley Periodicals, Inc. Head Neck 38:1263–1270, 2016